Note from Linda Carlson to Jack Curfman - Carlson, Linda, author (Colorado State University. Libraries, 1989)
Handwritten thank you note from Curator, Linda Carlson, to exhibit designer, Jack Curfman.
Keywords: Fashion -- History; Fashion -- Exhibitions